Genetic characterization of biopsy-proven myocarditis: a pilot study. (3rd October 2022) - Bueno Marinas, M; Baritussio, A; Cason, M; Celeghin, R; Giordani, A; Tarantini, G; Rizzo, S; Marcolongo, R; Basso, C; Iliceto, S; Pilichou, K; Caforio, A L P
Abstract: Background: Myocarditis is characterized by the presence of an inflammatory infiltrate in the myocardium with degenerative/necrotic changes of cardiomyocytes, not-related to ischemic damage. Its clinical presentation is extremely heterogenous1. Endomyocardial Biopsy (EMB) is the diagnostic gold standard and provides etiopathogenetic diagnosis. Biopsy-proven myocarditis may be infectious, mainly viral, toxic o non-infectious immune-mediated/autoimmune. A complex interplay between genetic factors, environmental triggers (i.e. viral infection) and the immune response of the host is postulated at the basis of different disease evolution2. Purpose: To determine the prevalence of pathogenic/likely pathogenic (P/LP) variants in cardiomyopathy-related genes in a well-characterized cohort of biopsy-proven myocarditis. Methods: Sixty-six biopsy-proven myocarditis-affected patients (mean age 51±9, 41 males) underwent screening of 200 genes related to inherited cardiomyopathies. Definite/moderate gene association with Dilated Cardiomyopathy (DCM)3 and Arrhythmogenic Cardiomyopathy4 was based on the ClinGen framework. Variant prioritization was carried out using American College of Medical Genetics and Genomics rules5. Correlation with presence of virus on endomyocardial biopsy by polymerase chain reaction, family history and serum anti-heart autoantibodies (AHA) and/or aintiintercalated-disk autoantibodies (AIDA) was appraised. Results: Nineteen of the 66 biopsy-proven myocarditis patients (28%) carried a P/LP variant in cardiac-related genes. Titin (TTN) was the most overrepresented gene accounting for 11% of cases (7/66), followed by Myosin Heavy Chain 7 (MYH7) and Myosin Binding Protein C3 (MYBPC3) each accounting for 3% of cases (2/66), respectively. Of note, 29 of the 66 of index cases (44%) referred family history for cardiomyopathy and/or sudden cardiac death. However only 13/29 patients with family history were genotype-positive (45%), indicating that other immunogenetic factors might contribute to triggering myocarditis. Circulating AHA and/or AIDA were detected in 31% of our genotype-positive cohort (6 of 19); a virus positive diagnosis was obtained in 15% of cases. Conclusion: The prevalence of clinically actionable P/LP variants in cardiomyopathy-related genes is nearly one third of biopsy-proven viral or autoimmune myocarditis patients, most of them associated with DCM. On the other hand, positive family history (44%) in the absence of known cardiomyopathy-related genes indicates that additional immunogenetic factors might contribute to disease pathogenesis. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministero della Salute - Italy - Ricerca Sanitaria Finalizzata